Identification and Indicators of ERP Implementation Success Factor – a Literature Review - Warih Puspitasari; Muhardi Saputra; R. Wahjoe Witjaksono (School of Industrial and System Engineering, Telkom University, 2021)
Enterprise Resources Planning has become one of the business and management applications that arebelieved to be able to improve the performance of companies and or organizations to be more efficientand effective. However, based on much research, the success rate of ERP implementation isquestionable. Although the success of ERP implementation is often published in research, the failurerate of ERP system implementation is relatively high. Therefore, this study is to find out the problemsand challenges faced by organizations in implementing ERP, by reviewing the existing literature onresearch on factors that influence the success of ERP implementation. The approach taken is to reviewseveral related research articles published in the 2015-2020 period from several publishers, namelyEmerald Online, Science Direct, IEEE, and SAGE. The sample size for the last 5 years is expected toshow the up-datedness of the data taken from the research article. New ideas that will emerge fromthis discussion are the main factors causing the success of ERP implementation for organization, sothat they can be used to reduce the failure rate of ERP implementation in the future by proposing anERP implementation model.